Huanglian Ejiao Decoction Alleviates Ulcerative Colitis in Mice Through Regulating the Gut Microbiota and Inhibiting the Ratio of Th1 and Th2 Cells - Tang J; Hu Y; Fang J; Zhu W; Xu W; Yu D; Zheng Z; Zhou Q; Fu H; Zhang W (Drug Design, Development and Therapy)
Jingyi Tang,1,2,* Yingnan Hu,1,3,* Jintao Fang,1,* Weihan Zhu,1,* Wenjun Xu,1 Dian Yu,1 Zhipeng Zheng,4 Qiujing Zhou,4 Huiying Fu,4 Wei Zhang1,4 1The Second Clinical Medical College of Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of China; 2Lanxi Hospital of Traditional Chinese Medicine, Jinhua, 321100, People’s Republic of China; 3The Sixth Affiliated Hospital, Sun Yat-Sen University, Guangzhou, 510510, People’s Republic of China; 4The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, 310005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Zhang; Huiying Fu, Email zhangweils1968@163.com; fhy131@126.comBackground: Huanglian-ejiao decoction (HED) is a Chinese traditional medicinal formula evolved from the Shanghan Lun (Treatise on Febrile Diseases). However, HED ultimate mechanism of action remained indistinct. Therefore, this study aimed to investigate whether HED could exert anti-inflammatory effects on 2,4,6-Trinitrobenzenesulfonic acid (TNBS)-induced colitis (UC) model through the regulation of CD4+T subsets and gut microbiota.Methods: Fifty-eight major compounds in HED were identified by UPLC-Q-TOF/MS. The therapeutic efficacy of HED on UC was assessed by evaluating survival rate and so on. Flow cytometry was employed to assay the percentages of CD4+T cell. RT-PCR and Western blot took advantage of detecting transcription factors, inflammatory factors, and tight junction proteins. Transcriptome sequencing was performed on colon tissue and 16S rRNA gene sequencing was enforced on intestinal contents.Results: The administration of HED enhanced the survival rate of colitis mice, significantly restored body weight, DAI score, colon weight and index, spleen weight and index. HED effectively reshaped intestinal barrier dysfunction, inhibited the ratio of Th1 to Th2 cells, and preserved Th2/Th1 and Tregs/Th17 balance. Moreover, HED notably decreased the secretion of transcription factors and related cytokines. Interestingly, HED also exerts regulatory effects on gut dysbiosis by cumulative the plenteous of beneficial probiotics like Lactobacillus and Bacteroides, while inhibiting the overgrowth of opportunistic pathogens such as Helicobacter.Conclusion: The regulation of Th2/Th1 and Tregs/Th17 cell balance, as well as the modulation of gut microbiota by HED, provides further experimental evidence for the feasibility of its treatment of UC.Keywords: HED, ulcerative colitis, Th2/Th1, Treg/Th17, gut microbiota